ISCHEMIC STROKE IN A CHILD WITH COMPLEX CYANOTIC CONGENITAL HEART DISEASE - Aniela Luminita Rugina; Violeta Streanga; Nicolai Nistor; Gabriela Buhusi; Ramona Filipescu; Irina-Mihaela Ciomaga (Amaltea Medical Publishing House, 2014)
Stroke is rare in children compared to adults. Most common causes of stroke in children are heart diseases that cause embolism and cerebral infarction and arteriovenous malformations for the brain hemorrhages, but a number of cases remain idiopathic, without being able to say precise etiology. The authors present the case of a child diagnosed in infancy with complex cyanotic heart malformation, but not operated, admitted with clinical and radiological signs of pneumonia, which evolved favorably with antibiotic and symptomatic therapy. During resolution of the pneumonia, the child becomes suddenly drowsy, presenting right hemiplegia, with absence of refl exes on the same side. Clinical examination correlated with cranio-cerebral CT have established the diagnosis of bilateral Sylvian ischemic stroke. The evolution was favorable under conservative treatment (antiplatelet drugs, physiotherapy), but right hemiplegia persisted.